Macroeconomics an Asian perspective - Froyen, Richard T.; Low, Linda (Prentice Hall, 2001)
Traces the history of macroeconomics, the evolution of macroeconomic thought, and the resulting theories and policies. All points of view are covered and the result is a comprehensive and detailed view of modern macroeconomic theory. This revised edition is "Asianized" to incorporate empirical evidence and illustrations from the major East Asian economies including Japan, the new-industrializing economies and the Association of Southeast Asian Nations.